PEMETAAN KEMAMPUAN PENULISAN MAKALAH SISWA KELAS IX SMP NEGERI 3 GALESONG SELATAN - Dzul Jalali Wal Ikram; Ratna Wati; Hajaratul Aswad; Riska; Elvi Ayu Nilam Sari (STKIP Subang, 2025)
This quantitative descriptive research was conducted with the main objective to comprehensively map and describe the level of essay writing ability of 9th grade students of UPT SMP Negeri 3 Galesong Selatan. The ability to write essays is considered an important prerequisite that measures students' critical thinking competencies and academic communication skills before continuing to higher levels of education. All 9th grade students in the academic year [Academic Year] were sampled through a total sampling technique or census (N=120). Data were collected through a practical essay writing test instrument, which was then analyzed based on a multi-aspect assessment rubric, including formative structure, content quality (content), grammatical and spelling accuracy, and citation and bibliography systems. The results of the analysis using descriptive statistics showed that students' overall essay writing ability was in the Sufficient category (Average Score = 61.8). Detailed aspect mapping showed a significant disparity in ability, with the highest score achieved in the Structure and Format aspect, while the lowest score was significantly in the Citation and Bibliography aspect (49.3%). These findings underscore the need for focused pedagogical interventions for teachers at the UPT SMP Negeri 3 Galesong Selatan to improve academic literacy, particularly in citation ethics and the application of formal writing rules.